The effect of Al2O3/PAG nanolubricant towards automotive air conditioning (AAC) power consumption - A. A., M. Redhwan; Wan Azmi, Wan Hamzah; M. Z., Sharif; N N M, Zawawi; O. W., Zulkarnain; Muhammad Aminullah, Abdul Rahman (IOP Publishing, 2019)
The usages of Automotive Air Conditioning (AAC) today is vital because of the hot and humid climate. The AAC is used to provide comfort in the automotive cabin temperature, consequently, increases fuel consumption, and release significant amount of CO2, and greenhouse gas into the air. Nanotechnologies could be employed into AAC system via lubricant compressor which can decrease power consumption, eventually increase power saving. The main objective of this paper is to experimentally investigate the effect of Al2O3/PAG nanolubricant onto the power consumption. The study on the stability and characteristic of the Al2O3/PAG nanolubricant has been done prior the experiment. The result shows that the Al2O3/PAG nanolubricant is stable event after 28 days with concentration ratio above 70%. The highest power saving percentage of 23.89% is achieved when the AAC system is operated with 0.010% Al2O3/PAG nanolubricant. Further, it has been shown that the condenser pressure and evaporator pressure are correlated with the increment of the power consumption with average deviation of 3.129% and 2.919%, respectively. Finally, the power consumption of AAC system reduce with the usage of the Al2O3/PAG nanolubricant at low concentration.